Toward Effective AI Support for Developers: A survey of desires and concerns. - Khemka, Mansi; Houck, Brian (Communications of the ACM, 2024)
This article details a survey conducted with software developers on their views on artificial intelligence (AI), how they want to use it in their work and what are their areas of excitement and areas of concerns about incorporating AI into their workflow. Additionally, the article presents ideas on how organizations and leaders can address developer concerns about AI.